THE VALUE OF INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN OF THE SUBJECT STUDY OF "AGE PHYSIOLOGY AND HYGIENE" (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
New pedagogical technologies used during lessons on infectious diseases are described, thanks to which students develop analytical thinking, as well as interest in scientific research and the desire to develop acquired skills.